Video Games and the Politics of Historical Memory: War Memory in American and Russian Video Games - Žukauskas, Aivaras (Politologija, 2018)
[only abstract in English; full article and abstract in Lithuanian]The video game industry has been growing rapidly in the recent years, reaching almost 2 billion players worldwide and sometimes even exceeding profits and other numbers put up by such entertainment juggernauts as the Hollywood. It is safe to say that video-games have become an integral part of contemporary popculture, contributing to the formation of attitudes, especially among younger audiences (18–35 years old). This is especially poignant in the case of historical games, which have always been popular and have been representing one or another version of historical narration for years.Nevertheless, despite the immense popularity of videogames and their growing presence within contemporary culture, historians, political and social scientists have been often neglecting video game studies primarily because of its infancy and inadequacy to provide space for political reflection and argumentation. According to the skeptics, video games can only reflect the current tendencies within the order of neoliberalism prevailing in the world. However, the article contradicts this by proposing to treat this situation as an opportunity instead of an excuse – the fact that video games can reflect the injustices of today’s world without providing criticism should act as a catalyst for further studies of political argumentation within the medium of video games, which in turn would contribute to further theorizations on the critical potential of video games in connection to politics. This is deemed especially important in the case of reconstructing historical narratives in the most popular video games, the majority of which focus on various historical instances of war. As a result, the first part of the article presents an analysis on both the potential and limitations of videogames to act as spaces for the commemoration of historical memory. The second part aims to ground the theoretical implications by considering to examples of video game industries – the United States and Russia – and techniques as well as directions that they employ in reconstructing the popular prosthetic memory related to wars in which these countries had participated.The article concludes with the idea that historical games can indeed act as a space for producing specific historical narratives oriented toward the popular memory. When it comes to American games, they mostly focus on presenting more personal stories regarding the heroic and virtuous American soldiers during a given War. This, supplemented by a diminished or exaggerated account of actions taken by other allies (as well as enemies) aims at whitewashing the American historical memory. Among the Russian games, however, personal identification through emotional storybuilding is much less pronounced. Its place is taken by focusing on the technological domination and de-personalized stories of bravery employed by the Russians and Soviets.To conclude, the article once again calls for more engagement with the medium of videogames from the side of social and political science as well as history. Video games have quickly become one of the main venues for younger demographic groups to get their first pieces of knowledge regarding history, politics, gender and other topics. The importance of this is understood not only by American but by Russian officials as well, which demands more research on the power of games and their critical potential. This engagement would allow for less political manipulation (especially in the case of historical games) and for a better understanding and fulfillment of the potential of video games.
Keywords: none